New records of Burgess Shale-type taxa from the middle Cambrian of Utah. (1st October 2015) - Conway Morris, Simon; Selden, Paul A.; Gunther, Glade; Jamison, Paul G.; Robison, Richard A.
Abstract: Cambrian strata of the Laurentian craton contain numerous examples of Burgess Shale–type faunas. Although displaying a more or less concentric distribution around the cratonal margin, most faunal occurrences are in present-day western North America, extending from the Northwest Territories to California. Nevertheless, the soft-bodied and lightly skeletalized fossils in most of these Lagerstätten are highly sporadic. Here, we extend knowledge of such Middle Cambrian occurrences in Utah with reports of four taxa. An arthropod from the Marjum Formation, Dytikosicula desmatae gen. et sp. nov., is a putative megacheiran. It is most similar to Dicranocaris guntherorum, best known from the younger Wheeler Formation, but differs primarily in the arrangement of pleurae and overall size. Along with a specimen of ? Yohoia sp, a new species of Yohoia, Y. utahana sp. nov., is described. It differs from the type and only known species, Y. tenuis, principally in its larger size and shorter exopods; it is the first description of this genus from outside the Burgess Shale. A new species of a stem-group lophotrochozoan from the Spence Shale, Wiwaxia herka sp. nov., possesses a palisade of dorso-lateral spines that are more robust and numerous than the type species of Wiwaxia, W. corrugata . Another notable taxon is Eldonia ludwigi from the Marjum Formation, which is interpreted as a primitive ambulacrarian (assigned to the cambroernids) and a new specimen of the ?cnidarian Cambrorhytium from the Wheeler Shale is illustrated.